PENGARUH KEPRIBADIAN TERHADAP KEPUTUSAN KONSUMEN MEMBELI PRODUK ROKOK CLAS MILD KOTA PALU - AFANDI, MUH. (Fakultas Ekonomi Universitas Tadulako, 2016)
The objective of this research is to know the effect of personality factor which consists of age dimension and life cycle stage, occupation and economic circumstances, personality and self-concept as well as lifestyle and values simultaneously and partial to the purchase of Clas Mild cigarette in Palu. The researcher takes 97 samples of respondents by using purposive sampling method, and data analysis tool used is multiple linear regression. Based on the result of multiple linear regression test, can be concluded: simultaneously the personality factor which consists of age dimension and life cycle stage, occupation and economic circumstances, personality and self-concept as well as lifestyle and values simultaneously and partial to the purchase of Clas Mild cigarette in Palu with the significant value F is 0,000 < 0.05. The age partial and life cycle stage, occupation and economic circumstances, personality and sellf-concpt as well as lifestyle and values are influenced significantly to the purchase of Clas Mild cigarette in Palu. The value of age and life cycle stage are 0.004 < 0.05, occupation and economic circumstance are 0.009 < 0.05, personality and self-concept are 0.027 < 0,05, life style and value are 0.02 < 0.05.